Probing the Diffuse Optical-IR Background with TeV Blazars Detected with the MAGIC Telescopes - Prandini, Elisa; Domínguez, Alberto; Fallah Ramazani, Vandad; Hassan, Tarek; Mazin, Daniel; Moralejo, Abelardo; Nievas Rosillo, Mireia; Vanzo, Gaia; Vazquez Acosta, Monica (Frontiers in Astronomy and Space Sciences, 2017)
Blazars are radio loud quasars whose jet points toward the observer. The observed emission is mostly non-thermal, dominated by the jet emission, and in some cases extends up to the very high energy gamma rays (VHE; E $>$ 100 GeV). To date, more than 60 blazars have been detected at VHE mainly with ground-based imaging atmospheric Cherenkov telescopes (IACTs) such as MAGIC, H.E.S.S. and VERITAS. Energetic photons from a blazar may interact with the diffuse optical and IR background (the extragalactic background light, EBL) leaving an imprint on the blazar energy spectrum. This effect can be used to constrain the EBL, with basic assumptions on the intrinsic energy spectrum. Current generation of IACTs is providing valuable measurements of the EBL density and energy spectrum from optical to infrared frequencies. In this contribution, we present the latest results obtained with the data taken with the MAGIC telescopes: using 32 spectra from 12 blazars, the scale factor of the optical density predicted by the EBL model from Domínguez et al. (2011) is constrained to be 0.95 (+0.11, -0.12)$_{stat}$ (+0.16, -0.07)$_{sys}$, where a value of 1 means the perfect match with the model.